If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + -5) = (7y + -9) Reorder the terms: 2(-5 + 5x) = (7y + -9) (-5 * 2 + 5x * 2) = (7y + -9) (-10 + 10x) = (7y + -9) Reorder the terms: -10 + 10x = (-9 + 7y) Remove parenthesis around (-9 + 7y) -10 + 10x = -9 + 7y Solving -10 + 10x = -9 + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 10x = -9 + 10 + 7y Combine like terms: -10 + 10 = 0 0 + 10x = -9 + 10 + 7y 10x = -9 + 10 + 7y Combine like terms: -9 + 10 = 1 10x = 1 + 7y Divide each side by '10'. x = 0.1 + 0.7y Simplifying x = 0.1 + 0.7y
| 5-4(3+5v)+8= | | 0.375x+4=0.66 | | -6+3k=4k-8 | | 6x-18=2x+12 | | 6(4v+2)=36 | | 1/9m-3=0 | | 5x+7y-4z=31 | | -x-11/3=21 | | (2x+40)+(5x+12)= | | w-4w-32=0 | | 4t=21 | | 2p^2+2p-9=0 | | 2x-y-1=o | | 0.045=x | | 0.5x-3=0.8 | | 2(x+2)-6=5x+1 | | 9k-2k+3k-6k=12 | | x-75/7.5=y | | 2(2w+7)=2w+7 | | y=.33(9x-18) | | 2a+7a+13a+(-5a)-15a-4=-10 | | 6=1/12x | | 3x-14/4=x-8 | | 5x+35=13x-5 | | 6x=12.24 | | 0.166x+2=0.33 | | 3x+(2x-6)=91.50 | | X-3(x-2)=7x-1(2x+5) | | -16x^2+44x+18=0 | | X(x+3x)=28 | | 2(4b+8)=4+6b | | 3t-(-12t)-15t+(-20t)-(-8)=-12 |